The fourth generation of academic Kazakh grammar - Mamynova, Bagdan K.; Slyambekov, Qymbat B.; Soltanbekova, Alfiya A.; Imangazina, Meruyert A.; Рамазанов, Talgat B. (The New Research of Tuva, 2024)
The article discusses the issue of compiling large grammatical works, including academic grammars. In particular, answers are sought for such questions as the following: What is the scientific character (style) of compiling fundamental grammatical works? What should their scientific apparatus, their design and structure look like? What research methods should be used? What is their target audience? In order to achieve this purpose, we carried out a comparison of academic grammars originating in the Soviet Union and those fundamental, voluminous grammatical works compiled according to the European-American model. The experience of compiling grammatical editions in Turkic languages has also been taken into account. The ideas obtained as a result were used in compiling the next academic grammar of the Kazakh language. This article was written with the objective of sharing the experience and elaborating on the results of the comparison.It has been found out that fundamental grammatical works have their own scientific character (this concerns the Soviet school): academic grammars are written on the normative and descriptive basis, i.e. scientific descriptions must be accompanied by a normative differentiation. The structure is directly linked to the levels of language which the editorial board have chosen as the object of study (lexis, phonetics, word building, morphology and syntax). There are consistency and moderation in designing grammatical works as well. Research material and examples are taken from literary samples. These principles are based on the fact that academic grammars are oriented to scientific and educational community. At the same time, as European and American fundamental grammars are compiled for the general scientific community, the aforementioned academic principles may not be followed.Since fundamental grammatical works are not compiled very often (once in 20–30 years), such studies are not frequent either. The grammars created in the Soviet period have not been revised fully yet. It is specifically important to revise academic grammars, as they need to document and standardize the new knowledge in the field of language. The issue of revising the academic grammar of the Kazakh language has been brought into the spotlight, and in 2022, the new generation of the grammar was prepared. For this reason, the conclusions of the article and the experience obtained while developing the new generation of the “Kazakh Grammar” may become useful while compiling new fundamental grammatical works.
Keywords: academic grammar; morphology; syntax; Kazakh grammar; grammatical structure; English grammar; Tatar grammar; Tuvan grammar; Turkish grammar; Kazakh language